Nanog mediates tobacco smoke‐induced enhancement of renal cancer stem cell properties. Issue 11 (10th July 2020) - Zhang, Taotao; Sun, Hongliang; Liu, Rui; Cao, Wanshuang; Zhang, Tao; Li, Enlai; Sun, Xianchao; Wu, Wangyu; Yu, Dexin; Zhong, Caiyun
Abstract: Nanog plays an important role in the regulation of cancer stem cells (CSCs) which participate in tumorgenesis and progression. In renal cancer, tobacco smoke (TS) is considered a major risk factor. However, the molecular mechanism by which TS induces the development of renal CSC properties remains largely unknown. In this study, we showed that the level of Nanog was elevated in renal cell carcinoma (RCC) patients with a smoking history, and that Nanog overexpression promoted the traits of CSCs in renal cancer. We further demonstrated that a 8‐week exposure of TS enhanced the formation of renal tumorspheres, increased the population of CD133‐positive cells, and stimulated the expression of Nanog and CSC markers. In addition, TS was found to play a role in accelerating the cell growth transition from G1 to S phase in renal CSCs. Finally, we demonstrated that the TS‐induced effects in renal CSCs could be reversed through the downregulation of Nanog. Our results suggested that Nanog plays a role in mediating TS‐induced renal CSC properties. This study may provide new insights into the molecular mechanism of TS‐related renal tumorigenesis, which can contribute to the future development of therapeutics for renal cancer.